2022
DOI: 10.3390/genes14010037
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Lipid Metabolomics Analysis of Subcutaneous, Visceral, and Abdominal Adipose Tissues of Beef Cattle

Abstract: Fat deposition traits are influenced by genetics and environment, which affect meat quality, growth rate, and energy metabolism of domestic animals. However, at present, the molecular mechanism of fat deposition is not entirely understood in beef cattle. Therefore, the current study conducted transcriptomics and lipid metabolomics analysis of subcutaneous, visceral, and abdominal adipose tissue (SAT, VAT, and AAT) of Huaxi cattle to investigate the differences among these adipose tissues and systematically exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…In this study, ACACA was found to be enriched in fatty acid biosynthesis and metabolism by bioinformatics analysis. Indeed, ACACA is a biotin-dependent enzyme [ 29 ], and the C-terminal carboxytransferase domain of ACACA catalyzes the carboxylation of acetyl-CoA to malonyl-CoA and, therefore, is involved in the fatty acid synthesis [ 30 ]. Thus, ACACA may also play an important role in estrus regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ACACA was found to be enriched in fatty acid biosynthesis and metabolism by bioinformatics analysis. Indeed, ACACA is a biotin-dependent enzyme [ 29 ], and the C-terminal carboxytransferase domain of ACACA catalyzes the carboxylation of acetyl-CoA to malonyl-CoA and, therefore, is involved in the fatty acid synthesis [ 30 ]. Thus, ACACA may also play an important role in estrus regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that ACACA has a significant impact on the fatty acid profiles of cattle, including C10:0, C14:0, and C13:0 [46][47][48][49]. In a transcriptomic and lipid metabolomic analysis of beef cattle, ACACA positively correlated with total MUFA [50]. In the Puławska breed (a Poland native pig breed originating from the Lublin region), ACACA exhibited a relationship with IMF content, with differences reaching 20% [51].…”
Section: Patterns Of Selection Signaturesmentioning
confidence: 99%
“…Gene transcripts undergo diverse splicing to generate various isoforms. With the commercialization of sequencing platforms and the reduced sequencing costs, transcriptome sequencing technology has found widespread application in animal transcriptome studies, including pigs [ 7 ], chickens [ 8 ], beef cattle [ 9 ], goats [ 10 ], and sheep [ 11 ]. Previous studies on sheep fat metabolism have primarily focused on short-read RNA-seq data from second-generation sequencing platforms [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%